1998
DOI: 10.1002/(sici)1097-4636(19980905)41:3<359::aid-jbm3>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombinant human bone morphogenetic protein-2 on the integration of porous hydroxyapatite implants with bone

Abstract: To determine if recombinant human bone morphogenetic protein-2 (rhBMP-2) can be adsorbed onto porous ceramic hydroxyapatite (HA) and promote the integration of HA to host bone, 54 subperiosteal pockets were created on the skulls of 19 adult Pasteurella-free white rabbits. Fourteen HA implants were saturated with saline and placed in subperiosteal pockets (control), 22 HA implants were saturated with saline and placed into subperiosteal pockets after burring 1-2 mm of calvarium to expose bleeding cancellous bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 22 publications
0
29
1
1
Order By: Relevance
“…The results of these studies have shown that carriers of BMP, such as collagen, [3][4][5] hydroxyapatite, 6 allogenic, 7 xenogenic, 8 and alloplastic 9,10 materials, improve the bone-regenerative efficacy of this protein compared with control findings.…”
contrasting
confidence: 65%
“…The results of these studies have shown that carriers of BMP, such as collagen, [3][4][5] hydroxyapatite, 6 allogenic, 7 xenogenic, 8 and alloplastic 9,10 materials, improve the bone-regenerative efficacy of this protein compared with control findings.…”
contrasting
confidence: 65%
“…The advantage of high porosity in scaffolds has been reported to achieve good cellular distribution, and that it is critical to select the correct pore size [63] . For example, it has been reported that increased HA porosity decreases its malleability and reduces its ability to conform to the irregular surfaces that may be present in host bone [42,[64][65] . This challenge may be overcome by re-engineering a porous HA to deliver bone inductive proteins such as recombinant human bone morphogenic protein 2 (rhBMP 2).…”
Section: In Vivo Characteristics / Clinical Studiesmentioning
confidence: 69%
“…It is important to note that the present study does not confirm an endochondral ossification path by means of the measured in vivo mechanical relaxation parameters for the rhBMP-2 treated group, as would have been suggested by some earlier studies (Yasko et al, 1992;Koempel et al, 1998;Einhorn et al, 2003;Edwards et al, 2004;Glatt et al, 2008;Yu et al, 2010). For instance, a study by Yasko et al (1992) that used a rat model similar to ours, demonstrated by weekly histological examination that the healing of rat segmental defects occurs via endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%